Asuhan Keperawatan Pasien Penurunan Kesadaran - Daeli, Weslei; Solehudin, Solehudin; Suryadi, Bambang (Barongko: Jurnal Ilmu Kesehatan, 2024)
Nursing care for patients with decreased consciousness is not only related to medical monitoring, but also involves holistic aspects such as emotional support and effective communication. This study aims to explain in depth nursing care for patients with decreased consciousness, including the challenges that nurses may face, effective intervention strategies, and the important role of nurses in improving the patient's quality of life. The method in this research uses a case study. The research method is nursing care which includes assessment, diagnosis, intervention, implementation and evaluation of nursing in 1 (one) shift. The results of the assessment showed that the patient's admission history arrived at the Emergency Room with a medical diagnosis of Chronic Kidney Disease. When the Somnolent consciousness assessment was carried out, GCS 10, the patient experienced respiratory failure, a ventilator was installed, OPA, NRM 10 lpm, an NGT was installed, the NGT fluid was yellow. The patient had a Folley catheter installed, the urine color was clear yellow. Physical examination; Blood pressure 124/82 mmHg, pulse 104x/minute, RR 13x/minute, temperature 370c, rhonchi wet. The main nursing problem found in these patients was gas exchange disorders. Nursing actions include ensuring the patient's airway remains open, providing respiratory assistance or mechanical ventilation, monitoring vital signs, such as blood pressure, pulse, breathing and body temperature, collaborating with health team members, such as doctors and therapists, to plan and provide effective care.